Generalized linear isotherm regularity equation of state applied to metals - Sun, H.; Sun, J.X.; Yu, W.J.; Tang, J. (Condensed Matter Physics, 2012)
A three-parameter equation of state (EOS) without physically incorrect oscillations is proposed based on the generalized Lennard-Jones (GLJ) potential and the approach in developing linear isotherm regularity (LIR) EOS of Parsafar and Mason [J. Phys. Chem., 1994, 49, 3049]. The proposed (GLIR) EOS can include the LIR EOS therein as a special case. The three-parameter GLIR, Parsafar and Mason (PM) [Phys. Rev. B, 1994, 49, 3049], Shanker, Singh and Kushwah (SSK) [Physica B, 1997, 229, 419], Parsafar, Spohr and Patey (PSP) [J. Phys. Chem. B, 2009, 113, 11980], and reformulated PM and SSK EOSs are applied to 30 metallic solids within wide pressure ranges. It is shown that the PM, PMR and PSP EOSs for most solids, and the SSK and SSKR EOSs for several solids, have physically incorrect turning points, and pressure becomes negative at high enough pressure. The GLIR EOS is capable not only of overcoming the problem existing in other five EOSs where the pressure becomes negative at high pressure, but also gives results superior to other EOSs. Запропоновано трипараметричне рiвняння стану без фiзично некоректних осциляцiй, що базується на узагальненому потенцiалi Леннарда-Джонса (GLJ) i пiдходi Парсафара i Мейсона [Parsafar G.A., Mason E.A., J. Phys. Chem., 1994, 49, 3049] до виведення рiвняння стану з регулярнiстю лiнiйної iзотерми (LIR). Запропоноване узагальнене рiвняння стану може включати в себе LIR рiвняння стану як частковий випадок.
Трипараметрична узагальнена регулярнiсть лiнiйної iзотерми [Parsafar G.A., Mason E.A., Phys. Rev. B, 1994, 49, 3049] (PM), [Shanker J., Singh B., Kushwa S.S., Physica B, 1997, 229, 419] (SSK), [Parsafar G.A., Spohr H.V., Patey G.N., J. Phys. Chem. B, 2009, 113, 11980] (PSP) i переформульованi PM SSK рiвняння стану є застосованi до 30 металiчних твердих тiл у широкiй областi тиску. Показано, що PM, PMR i PSP рiвняння стану для бiльшостi твердих тiл та SSK i SSKR рiвняння стану для декiлькох твердих тiл мають фiзично некоректнi поворотнi точки, i тиск стає негативним при досить високому тиску. Узагальнене рiвняння стану є здатним не тiльки подолати проблему, iснуючу в iнших п’яти рiвняннях стану, де тиск стає негативним при високому тиску, але також дає кращi результати, нiж iншi рiвняння стану.